2020
DOI: 10.1111/tme.12667
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐hospital transfusion of red blood cells. Part 1: A scoping review of current practice and transfusion triggers

Abstract: Objectives: The primary aim of this scoping review is to describe the current use of pre-hospital transfusion of red blood cells (PHTRBC) and to evaluate criteria used to initiate PHTRBC. The effects on patients' outcomes will be reviewed in Part 2.Background: Haemorrhage is a preventable cause of death in trauma patients, and transfusion of red blood cells is increasingly used by Emergency Medical Services (EMS) for damage control resuscitation. However, there are no guidelines and little consensus on when to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 87 publications
(150 reference statements)
0
22
0
4
Order By: Relevance
“…The search in PubMed and Web of Science yielded 2172 hits after removal of duplicates. In our scoping review, 71 articles were included . In total, 55 of these studies reported one or more outcome measure, and were included in this review (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search in PubMed and Web of Science yielded 2172 hits after removal of duplicates. In our scoping review, 71 articles were included . In total, 55 of these studies reported one or more outcome measure, and were included in this review (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…PubMed and Web of Science were searched through January 2019. The search strategy and the process of selection of studies were described previously . For the purpose of this systematic review, only the manuscripts reporting outcome measures after PHTRBC (data on the hemodynamic state, coagulopathy, 24 hours RBC transfusion requirement, length of stay in hospital/intensive care unit [ICU], mortality, or occurrence of complications) were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this edition, we present a two‐part review of the use of red cells in pre‐hospital care from van Turenhout et al, a Dutch clinical team. The first part reviews current practice including the transfusion triggers to treat . The second paper is a systematic review of pre‐hospital red cell transfusion on clinical outcomes .…”
Section: Reviewing the Evidencementioning
confidence: 99%
“…Pre‐hospital blood products (PHBPs), including freeze‐dried plasma, are increasingly carried on air ambulance helicopters in the United Kingdom 1 . In other countries, 25% of programs currently carry blood, although others have stopped owing to logistical challenges 2 . The helicopter working environment has more noise, vibration, and greater temperature extremes than that of ground emergency medical services (GEMS).…”
Section: Introductionmentioning
confidence: 99%